2019
DOI: 10.18203/2319-2003.ijbcp20195296
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters and neuromodulators involved in learning and memory

Abstract: Learning and memory being highly specialized process of human brain involves complex interaction between neurotransmitters and cellular events. Over the years, the understandings of these processes have been evolving from psychological, neurophysiological, and pharmacological perspectives. The most widely appraised model of learning and memory involves attention, acquisition, storage and retrieval. Each of these events involve interplay of neurotransmitters such as dopamine, acetylcholine, norepinephrine, N-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Neurotransmitter is the major signaling molecule secreted by a neuron to communicate with other cells across a synapse to facilitate learning and memory function in the hippocampus [ 39 , 40 ]. We investigated the role of TG in modulating neurotransmitters in SAMP8 mice hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitter is the major signaling molecule secreted by a neuron to communicate with other cells across a synapse to facilitate learning and memory function in the hippocampus [ 39 , 40 ]. We investigated the role of TG in modulating neurotransmitters in SAMP8 mice hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…The total intake of protein and fat influenced recollection accuracy. The effect of proteins on memory could be explained by the fact that proteins consist of long chains of amino acids that are divided up during digestion, and some of these amino acids are precursors of neurotransmitters involved in memory ( Bairy and Kumar, 2019 ). In particular, the amino acid glutamine is a precursor of glutamate, and the amino acids phenylalanine and thyrosine are precursors of dopamine, which in turn is a substrate of norepinephrine ( Fernstrom, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, soy proteins acutely increased CBF after consumption of isolated soy proteins (8 g), which may be due to beneficial effects on neurotransmission (130) and NO metabolism (131). Neurotransmitter systems are involved in brain functions, such as learning and memory processes (132), while NO is an important intercellular messenger in cerebral and peripheral hemodynamics (133). In Chapter 6, we concluded that the function of the regions with increased CBF may be related to the psychomotor speed domain, suggesting a potential mechanism by which an increased intake of soy rich foods beneficially affects cognitive performance in older males and females.…”
Section: Soy Supplementationmentioning
confidence: 99%